ER-Mitochondria Calcium Flux by β-Sitosterol Promotes Cell Death in Ovarian Cancer - Hyocheol Bae; Sunwoo Park; Jiyeon Ham; Jisoo Song; Taeyeon Hong; Jin-Hee Choi; Gwonhwa Song; Whasun Lim (MDPI AG, 2021)
Phytosterols, which are derived from plants, have various beneficial physiological effects, including anti-hypercholesterolemic, anti-inflammatory, and antifungal activities. The anticancer activities of natural products have attracted great attention, being associated with a low risk of side effects and not inducing antineoplastic resistance. β-sitosterol, a phytosterol, has been reported to have anticancer effects against fibrosarcoma and colon, breast, lung, and prostate cancer. However, there are no reports of its activity against ovarian cancer. Therefore, we investigated whether β-sitosterol shows anticancer effects against ovarian cancer using human ovarian cancer cell lines. We confirmed that β-sitosterol induced the apoptosis of ovarian cancer cells and suppressed their proliferation. It triggered pro-apoptosis signals and the loss of mitochondrial membrane potential, enhanced the generation of reactive oxygen species and calcium influx through the endoplasmic reticulum-mitochondria axis, and altered signaling pathways in human ovarian cancer cells. In addition, we observed inhibition of cell aggregation, suppression of cell growth, and decreased cell migration in ovarian cancer cells treated with β-sitosterol. Further, our data obtained using ovarian cancer cells showed that, in combination with standard anti-cancer drugs, β-sitosterol demonstrated synergistic anti-cancer effects. Thus, our study suggests that β-sitosterol may exert anti-cancer effects against ovarian cancer in humans.